REFLECTION OF FEUDAL SOCIETY IN ROBIN HOOD AND TRANSMISSION OF OUTLAW CULTURE (Web of Teachers: Inderscience Research, 2024)
This article examines the depiction of feudal society and outlaw culture in Robin Hood's time in The Ballad of Robin Hood. It can be said that some taxes paid by the people were not included in the law and the money collected from these taxes was taken away by some government officials. The article serves to reveal exactly such hidden situations.